액화수소 탱크의 단열시스템 적용을 위한 진공 기술의 실험적 분석 - 차승주; 황병관; 김희태; 이경훈; 박한솔; 김정현; 이제명; Seung-Joo Cha; Byeong-Kwan Hwang; Hee-Tae Kim; Gyung-Hun Lee; Hans-Sol Park; et al. (大韓造船學會 論文集, 2025)
This study aims to develop technological procedures for establishing a vacuum environment in the vacuum insulation systems of liquid hydrogen tanks. The insulation performance of such systems is highly influenced by the vacuum level, necessitating experiments across low, medium, and high vacuum ranges. However, achieving a vacuum environment in the structural unit of a large thermal vacuum chamber poses significant challenges, particularly due to the impact of moisture outgassing under high vacuum conditions. To address these issues, experiments were conducted to optimize the vacuum environment and enhance the evacuation rate, successfully achieving target performance up to the ultra-high vacuum level. Based on these findings, a vacuum heating system was introduced to facilitate the creation of high vacuum environments, and a comprehensive vacuum technology procedure was established.